Los Caprichos, de Francisco Goya: manifestações da sombra coletiva espanhola - Nunes, Cristina Accioly (2013)
The purpose of this dissertation is to understand and analyze the engravings of the series called Los Caprichos, created by Spanish painter and engraver Francisco José de Goya y Lucientes, we have as hypothesis that it seems to represent aspects of the collective shadow of the Spanish society in the XVIII century. The theoretical support was based on the emerging concept of cultural complexes and the junguian premises that Art can compensate the collective conscious attitude of a particular society, in a particular moment of history. To the analysis we have picked categories, which have been obtained crossing the categories described in the specific literature of the Los Caprichos with articles available in the data bases of Scholar Google, SciELO, PePSIC e LILACS, narrowing down to four main collective shadow aspects: misogyny, the apathy of the Spanish aristocracy, the ignorance of the people and the power abuse of the clergy, which were subdivided into ten subcategories. To each subcategory, we have chosen one image of the series and analyzed through the symbolic amplification method. The results of the research suggest that, through caricature and satire, Goya has depicted many aspects of the Spanish collective shadow, of the XVIII century